2022
DOI: 10.1111/mve.12580
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pyrethroid resistance mutations and intron variants in the voltage‐gated sodium channel of Aedes (Stegomyia) aegypti and Aedes (Stegomyia) albopictus mosquitoes from Lao People's Democratic Republic

Abstract: In Lao People's Democratic Republic, Aedes aegypti (Linnaeus 1762) and Aedes albopictus (Skuse 1894) mosquitoes (Diptera: Culicidae) are vectors of arboviral diseases such as dengue. As the treatment for these diseases is limited, control of the vectors with the use of pyrethroid insecticides is still essential. However, mutations in the voltage‐gated sodium channel (vgsc) gene giving rise to pyrethroid resistance are threatening vector control programs. Here, we analysed both Ae. aegypti and Ae. albopictus mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 52 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…It is a sort of mystery that the L982W substitution has never been identified in the recent studies of A. aegypti from at least 16 regions of the neighboring countries: Thailand, Laos, and China, although this substitution was focused ( Fig. 4 ) ( 15 , 39 , 40 ). L982W was also not detected from 442 A. aegypti collected from three regions of Nepal in 2017 and 2018 ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a sort of mystery that the L982W substitution has never been identified in the recent studies of A. aegypti from at least 16 regions of the neighboring countries: Thailand, Laos, and China, although this substitution was focused ( Fig. 4 ) ( 15 , 39 , 40 ). L982W was also not detected from 442 A. aegypti collected from three regions of Nepal in 2017 and 2018 ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…S3 for the actual frequencies of all five alleles of Vgsc in the populations from Phnom Penh. No L982W substitution was detected from the cities marked with blue plots in China, Laos, Thailand, and Malaysia although the L982 was targeted (15,39,40). Note that L982W has never been detected in the Indochina Peninsula except Vietnam and Cambodia.…”
Section: Molecular Modeling Ofa Aegypti Vgscmentioning
confidence: 99%
“…The tenth intron 20 sequence consists of 237 bp and is identical to the previously characterized intron B variant [46] found in Ae. aegypti from Laos [37]. None of the intron variants observed here were identical to any of the four variants seen in Ae.…”
Section: Detection Of Mutations and Intron Variants In The Voltage-ga...mentioning
confidence: 38%
“…Mutation at the 410, 989, 1016, 1520, and 1534 amino acid positions in domains I, II, and III of the VGSC were detected in Asia in Ae. albopictus mosquitoes from China, Laos, Taiwan, Thailand, and Vietnam [30,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, five different introns were found in Domain III, of which two introns consisted of 68 and 70 bp, respectively, and the other three introns each consisted of 83 bp [ 52 ]. In the present study, introns A, B, and E were consistent with those in this previous study [ 52 ], although two other introns, referred to as C and D, were also found. The types of introns appear to play an important role in the regulation of gene mutation, but how this effect occurs remains unclear.…”
Section: Discussionmentioning
confidence: 99%